Peningkatan keterampilan komunikasi tertulis menggunakan model pembelajaran inkuiri terbimbing pada pembelajaran ipa - Atmojo, Idam Ragil Widianto; Saputri, Dwi Yuniasih; Bekti, Akhirul Yunita (Jurnal Pendidikan Dasar, 2023)
This study aims to improve written communication skills using the guided inquiry learning model in science learning.. This type of research is action research or Classroom Action Research (PTK). The research will be carried out in 3 cycles with 2 meetings and 1 evaluation test in each cycle. The implementation of guided inquiry learning in class V science subjects at SD Negeri Joho 1 went well and showed an increase in students' communication skills from cycle I, cycle II, to cycle III. 90% percentage to ask questions, 86% formulate hypotheses, 82% collect data, 84% analyze data, and 84% draw conclusions. The results of the assessment of student posters at the end of each learning cycle showed the category was less skilled (11.32) in cycle I, became quite skilled (17.08) in cycle II, and became skilled (23.84) in cycle III. This shows that the guided inquiry learning model improves students' communication skills.